The comparison of skin irritation level between topical cajeput oil and telon oil: A pilot study - Ilona, Sri Esa; Cahyono, Aris; Ellistasari, Endra Yustin; Irawanto, Muh. Eko; Kariosentono, Harijono (UI Scholars Hub, 2018)
Background: Cajuputi/Cajeput/Melalueca leucadendron oil is a type of essential oil, widely known and used by Indonesian for infants, children, and elderly. It is also included in telon oil compositions (±42%). Excessive application of cajeput oil and telon oil may lead to skin irritation. Methods: This randomized single-blind control trial was conducted with 10 subjects who met the inclusion criteria. Four areas with diameter of 10 mm each were made on the flexor surface of the upper arm. Area 1 was designated as negative control. Area 2 to 4 were pre-irritated with tape stripping for 40 ± 10 times using Nachitape®, followed by repeated open application test (ROAT) with cajeput oil, telon oil and alcohol (positive control). The skin irritation was examined in 15 minutes after each cycle by measuring transepidermal water loss (TEWL) using Tewameter® TM300 (Courage-Khazaka, Germany) and erythema using Mexameter® MDD4. Data were analyzed using One-way ANOVA with p<0.05 considered significance. Results: The average TEWL and erythema of cajeput oil (15.59; 345.42) were the highest compared to telon oil (12.63; 316.60), alcohol (13.87; 319.06) and negative control (7,48; 296.68). All treatment groups had significant differences in TEWL (p<0.000) and erythema (p<0.002) when compared to the negative control. However, cajeput oil showed the largest difference. Conclusion: Cajeput oil caused the most irritation compared to alcohol and telon oil. Therefore, it should be used with caution.